(untitled) (Revista Internacional de Folkcomunicação, 2020)
This article aims at point out a range of style within the Mexican director Carlos Reygadas’ films, namely Japón (2002) and Post tenebras lux (2012). We highlight the modes stylistic constants, such as the taste for inland stories, the equivalence between power and violence among subalterns characters, the alcoholism, the tragic expedient, circularities, and so on. As theoretical support we read Fredric Jameson (1982), Fausto Colombo (1986), Fiedrich Nietzsche (1992), and Pierre Bourdieu (2015). Suma; Style; History; Unconscious; Violency.